WHAT KIND OF UNIVERSITY RANKING SYSTEM WE NEED - Maria V. Seroshtan; Boris M. Vladimirsky (Moscow Polytechnic University, 2022)
Taking recent international university ranking trends into account, an analysis of requirements to a ranking system for Russian higher educational institutions was conducted. These requirements were considered in the context of the increase of the competitiveness of Russian universities while retaining the national identity of higher education.